1977
DOI: 10.1002/1097-4679(197701)33:1+<292::aid-jclp2270330166>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Alpha wave biofeedback training therapy in alcoholics

Abstract: This investigation evaluated the therapeutic efficacy of alpha-wave biofeedback treatment for alcoholics. Twenty-five Ss were compared to a matched control group before and after administration of a 3-week alpha-wave biofeedback regimen on a wide variety of criteria that included State-Trait Anxiety, the MMPI, Multiple Affect Adjective Check List, Zuckerman's Sensation Seeking Scale, Watson's Anhedonia Scale, the Brief Psychiatric Rating Scale, and baseline alpha. The experimental Ss received 10 hour-long alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Passini, Watson, Dehnel, Herder, and Watkins (1977) compared 25 anxious alcoholics with a matched control group before and after 10 h (over a 3 week period) of alpha neurofeedback training. Alpha neurofeedback training produced significant (p < 0.001) changes in state and trait anxiety compared with controls.…”
Section: Neurofeedback For Anxietymentioning
confidence: 89%
“…Passini, Watson, Dehnel, Herder, and Watkins (1977) compared 25 anxious alcoholics with a matched control group before and after 10 h (over a 3 week period) of alpha neurofeedback training. Alpha neurofeedback training produced significant (p < 0.001) changes in state and trait anxiety compared with controls.…”
Section: Neurofeedback For Anxietymentioning
confidence: 89%
“…Of the eight studies of anxiety that were reviewed, seven found positive changes. Another study (Passini, Watson, Dehnel, Herder, & Watkins, 1977) used only 10 hr of neurofeedback with anxious alcoholics and found very significant improvements in state and trait anxiety compared to a control group, with results sustained on 18-month follow-up. A randomized, blinded, controlled study was done with performance anxiety at London's Royal College of Music.…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…There were reported several uncontrolled case studies and conceptual reviews on alpha EEG training for alcohol (DeGood & Valle, 1978;Denney, Stelson, & Hardt, 1991;Jones & Holmes, 1976;Passini et al, 1977;Tarbox, 1983;Watson, Herder, & Passini, 1978) and drug abuse treatment (Brinkman, 1978;Goldberg, Greenwood, & Taintor, 1976Lamontagne, Beausejour, Annable, & Tetreault, 1977;Sim, 1976), but the impact of alpha biofeedback training as a SUD therapy was not significant.…”
Section: Studies Of Eeg Biofeedback In Substance Abuse Treatmentmentioning
confidence: 99%